GAMBARAN KERASIONALAN PENGOBATAN PADA PASIEN DEMAM BERDARAH DENGUE DI RUANG RAWAT INAP RSI SITI KHADIJAH PALEMBANG TAHUN 2017 - Masnir Alwi; Monica Julianti; Yunilda Rosa (Jurnal Kesehatan : Jurnal Ilmiah Multi Sciences, 2019)
The case of dengue fever (DF) is one of the health problems in the world which its prevalence increased hence the accuracy of therapy is needed to reduce morbidity. One one aspects that related to this is rationality treatment. This study aims to obtain an overview of rationality treatment in patients who suffered dengue fever (DF) in the Islamic Hospital Siti Khadijah Palembang in 2017. This research is a non-experimental research. The research subjects were all the patients who were diagnosed with dengue fever at the Siti Khadijah Islamic Hospital Palembang in 2017. The data was take based on medical record, the used data were retrospective data which were taken by using purposive sampling technique. The obtained data were 30 respondents who met the inclusion-exclusion criteria. The data analysis used is univariate analysis. The result showed that there was an inaccurate dose of (6.66%). A description of the rationality of treatment carried out from 30 patient stated that treatment rationality was (93,33%) and treatment irrationality was (6,66%). It is suggested that efforts be made to increase compliance for health professionals in hospitals in the completeness of recording in medical records.